Italian Neorealism : A Cultural History - Leavitt, Charles L., IV (Book collections on Project MUSE., 2020)
"Neorealism emerged as a cultural exchange and a field of discourse that served to shift the confines of creativity and revise the terms of artistic expression not only in Italy but worldwide. If neorealism was thus a global phenomenon, it is because of its revolutionary portrayal of a transformative moment in the local, regional, and national histories of Italy. At once guiding and guided by that transformative moment, neorealist texts took up, reflected, and performed the contentious conditions of their creation, not just at the level of narrative content but also in their form, language, and structure. Italian Neorealism: A Cultural History demonstrates how they did so through a series of representative case studies. Recounting the history of a generation of artists, this study offers fundamental insights into one of the most innovative and influential cultural moments of the twentieth century."--